Case Report: Pathogenic MYH9 c.5797delC Mutation in a Patient With Apparent Thrombocytopenia and Nephropathy - Ren, Pingping; Chen, Hongjun; Wang, Yucheng; Wang, Cuili; Feng, Shi; Jiang, Hong; Chen, Jianghua (Frontiers in Genetics, 2021)
MYH9-related disease or disorder (MYH9-RD) is an autosomal dominant disease caused by mutations in the MYH9 gene. Mutations in this gene initially affect the hemic system, and other manifestations may evolve with age. Here, we report the case of a 46-year-old Chinese woman with MYH9-RD who was primarily misdiagnosed with idiopathic thrombocytopenia purpura. Exome sequencing of the patient and the patient’s mother and son revealed a deletion mutation c.5797delC (p. R1933Efs*15) in exon 41 (encoding non-helical tailpiece, NHT) of the MYH9 gene, which consequently led to a frameshift mutation. To the best of our knowledge, this mutation has been reported in Italy once, while the substitution mutation c.5797 C>T is the most frequent mutation. Mutations that affect the NHT region cause thrombocytopenia throughout life; however, our patient presented with a more severe phenotype than previously reported, including thrombocytopenia, inclusion bodies in neutrophils, sensorineural hearing loss, nephropathy, and abnormal liver enzymes. Our goal in the current case is to prevent further progression of renal involvement and to identify other affected members in this family to provide early intervention. This case may raise awareness of MYH9-RD when diagnosing thrombocytopenia and improve our understanding of this condition.